2014
DOI: 10.1097/igc.0000000000000171
|View full text |Cite
|
Sign up to set email alerts
|

Radical Surgery in Patients With Residual Disease After (Chemo)Radiation for Cervical Cancer

Abstract: More radical surgery in patients with (minimal) central residual disease identified by routine biopsy 8 to 10 weeks after (chemo)radiation does not improve survival and should not be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 13 publications
1
49
0
1
Order By: Relevance
“…The most common severe adverse events include urinary tract injury (20%–26%), fistula formation (17%–28%), and ureteral stenosis. Although no treatment‐related deaths occurred in the present study, severe postoperative adverse events were observed in 27% of the patients treated with RH‐AR and were more frequent than among patients treated with P‐RH; this was in agreement with previous reports . The most common severe adverse events experienced by patients who underwent RH‐AR in the present study were also consistent with those described in previous reports (i.e., urinary tract injuries, fistula formation, and ureteral stenosis).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The most common severe adverse events include urinary tract injury (20%–26%), fistula formation (17%–28%), and ureteral stenosis. Although no treatment‐related deaths occurred in the present study, severe postoperative adverse events were observed in 27% of the patients treated with RH‐AR and were more frequent than among patients treated with P‐RH; this was in agreement with previous reports . The most common severe adverse events experienced by patients who underwent RH‐AR in the present study were also consistent with those described in previous reports (i.e., urinary tract injuries, fistula formation, and ureteral stenosis).…”
Section: Discussionsupporting
confidence: 92%
“…One of the major clinical issues associated with RH-AR is the high incidence of treatment-related morbidity. [10][11][12][13][14] Previous studies have reported severe postoperative adverse events occurring in 27%-64% of patients, along with postoperative deaths (Table S1). The most common severe adverse events include urinary tract injury (20%-26%), fistula formation (17%-28%), and ureteral stenosis.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The remaining 12 (80%) patients underwent hysterectomy unnecessarily. Boers et al reported the outcome of curative surgery for patients with residual tumor on histology following chemoradiotherapy and only two-thirds of the patients had residual tumor on hysterectomy specimen 8. Azria et al reported on patients with histology proven bulky residual disease following radiotherapy who were subsequently managed with adjuvant hysterectomy 9.…”
Section: Discussionmentioning
confidence: 99%